Indonesian EFL Teachers in the Swing of Curricula - Ashadi, Ashadi (Widya Mandala Catholic University Surabaya, 2015)
In the era of standard-based education which is marked by the reforms in many areas of education including curriculum, it is necessary to understand how Indonesian EFL teachers coped with curricular change in the course of their profession. This study attempts to discover how EFL teachers in Indonesia perceive the curricular changes through their beliefs, attitudes, and practices. Employing an on-line survey combined with semi-structured individual interviews, the qualitative study began with mapping EFL teachers’ generic perceptions towards curricular change. The initial map was then used to probe major emergent themes through individual interviews on purposively selected participants. The result showed that: (1) teachers’ belief was perceived to reshape through adequate socialization and training. (2), it took time to witness teachers’ belief formation and eventually attitudinal change, and (3) as their beliefs and practices were reshaped, teachers’ practice was highly likely to change moreover when improvement in learning gains were achieved by the students. However, the latter is often dismayed by the implementation of high-stakes testing (The National Examinations). This article is closed with relevant recommendations based on the particular findings. Keywords: Curricular change, teacher belief, teacher practice, qualitative